2017
DOI: 10.3349/ymj.2017.58.5.1018
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cortical Thickness in the Temporal Pole, Insula, and Pars Triangularis in Patients with Panic Disorder

Abstract: PurposeRecent neuroimaging findings have revealed that paralimbic and prefrontal regions are involved in panic disorder (PD). However, no imaging studies have compared differences in cortical thickness between patients with PD and healthy control (HC) subjects.Materials and MethodsForty-seven right-handed patients with PD who met the diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders-4th edition-text revision, and 30 HC subjects were enrolled. We used the FreeSurfer software packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…The olfactory cortex in the AAL template corresponds most closely to subcallosal gyrus in the Harvard-Oxford Maximum Probability Atlas, and contains portions of Brodmann Area 25, which is strongly implicated in the neurobiology of refractory depression (108). Thickness of the pars triangularis correlates with severity ratings in patients with panic disorder (109). Further, the pars triangularis contains a portion of Broca's area and could potentially play a role in the self-castigating 'voices' that maltreated individuals often perceive.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory cortex in the AAL template corresponds most closely to subcallosal gyrus in the Harvard-Oxford Maximum Probability Atlas, and contains portions of Brodmann Area 25, which is strongly implicated in the neurobiology of refractory depression (108). Thickness of the pars triangularis correlates with severity ratings in patients with panic disorder (109). Further, the pars triangularis contains a portion of Broca's area and could potentially play a role in the self-castigating 'voices' that maltreated individuals often perceive.…”
Section: Discussionmentioning
confidence: 99%
“…Based on neuroanatomy, 34 distinct cortical regions were then segmented for each hemisphere, according to the Desikan–Killiany Atlas . For our ROI‐defined cortical thickness analysis, masks for the bilateral STG were extracted from these 34 regions …”
Section: Methodsmentioning
confidence: 99%
“…The pars triangularis plays an important role in object recognition and labeling (Naeser et al, 2011); previous work has also shown that inhibition of response to emotional face cues in particular has been associated with increased IFG (and response inhibition in general, through connection with the pre-SMA), perhaps suggesting an effortful control of hyper-response in individuals with AUD but without anxiety (Schulz et al, 2009). On the other hand, studies have found that pars triangularis structural atrophy in schizophrenia is associated with poor recognition of angry faces (Maat et al, 2016), and that individuals with panic disorder have lower cortical thickness in the pars triangularis (Kang et al, 2017), consistent with the lack of distinction between emotional face processing in individuals with both AUD and anxiety traits here.…”
Section: Discussionmentioning
confidence: 99%